Evaluating effects of various mineral admixtures when replaced with a part of cement in concrete. Issue 1 (April 2021) - Sharma, Ujjwal; Yadav, Bhuvnesh; Gupta, Nakul
Abstract: With increase in the demand of concrete there is increase in demand of cement. Manufacturing cement leads to emission of harmful gases like carbon-di-oxide. This emission of harmful gases in environment led to global warming. On another hand increasing waste landfills of different materials such as brick-dust, ceramic-dust, husk-ash and many more leads to environmental pollution. Hence to save the environment from the harmful gases and also from increasing landfills we make use of various waste material termed as pozzolans. In the pre-requisite research we had taken three different pozzolans say china-clay, flue-ash and brick-kiln-powder. All the three pozzolans were replaced with the part of cement in concrete. The replacement was done to evaluate the pozzolans effect on concrete. The pozzolans are replaced in various set proportions. The replacement proportions were 3%, 6%, 9%, 12%, 15%, 18% and 21%. The concrete developed using various proportions of different pozzolans were tested for various test. The tests were done on fresh concrete and also after concrete get hardened. The tests conducted were C-S, S-T-T, and workability test. In total 189 cubes samples and 189 cylinder samples were casted. The investigation at last concluded that 12% of china clay, 21% of flue-ash and 18% of brick-kiln-powder separately when replaced with cement showed tremendous results as compared to normal concrete. Both C-S and S-T-S were seen to be increasing in same pattern. As the proportion of china-clay increases in concrete the value of slump tends to decrease. But in case of flue-ash it was increasing with increase in % replacement of flue-ash. The slump value in case of brick kiln powder assumed to be higher at 12% replacement. Hence, it was concluded that use of pozzolans in concrete in replacement to cement is good.